The other face of the coin : a reevaluation of the air war over Malaya 1941-42 - Cheang, Jia Wei (Nanyang Technological University, 2022)
The motif of under preparedness has been a recurring theme when examining the course of the air war over Malaya during World War Two. The common accusation being that modern aircraft would have done better than the obsolescent aircraft that were shot down in droves over the course of the seventy-day campaign. This is generally applied to the service history of the primary air defence aircraft of the Royal Air Force (RAF) Far Eastern Command (FEC) – the Brewster Buffalo. However, the Buffalo was never as terrible of a fighter as claimed by some as even more advanced aircraft such as the Hawker Hurricane and even the Supermarine Spitfire did not do well against the Japanese aircraft it encountered either. This essay thus attempts a reappraisal of the RAF’s position in the Far East by rejecting ‘European’ standards of aircraft performance. In tandem with this argument, this paper will also examine how the Japanese prepared for the war against Britain, specifically their preparation for a stronger RAF element. If one wishes to make the case of counterfactuals, one must account for the fact that their opponent will not remain static in their actions. This essay attempts to do just that.